Akkalomba: Upacara Adat Masyarakat Tanatoa Kajang Kabupaten Bulukumba - Risma Ariyani (Rayhan Intermedia, 2018)
This study aims to determine the background, processes and values ​​contained in traditional ceremonies Akkalomba in Tana Toa Village, District Kajang, Bulukumba Regency. This research uses in-depth interview technique, observation, and documentation. The results show that the Akkalomba ceremonial arises because of the religious emotion felt by the community so that they believe the truth of the myth contained in the pairs. The implementation process consists of two stages, namely the preparation stage: conducting deliberation, choosing good days, gathering firewood, inviting, cooking process and Assolo Berasa. The implementation process consists of: Conduct A'ngada ', bathing the child, praying offerings, and put Kampalo on both arms of the child. These ceremonies contain spiritual values, moral values, the value of solidarity and aesthetic value.